2011
DOI: 10.1016/j.jelectrocard.2011.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Second statement of the Working Group on Electrocardiographic Diagnosis of Left Ventricular Hypertrophy

Abstract: The Working Group on Electrocardiographic Diagnosis of Left Ventricular Hypertrophy, appointed by the Editor of the Journal of Electrocardiology, presents the alternative conceptual model for the ECG diagnosis of left ventricular hypertrophy (LVH). It is stressed that ECG is a record of electrical events, not of mechanical events and/ or anatomical characteristics. Considering the electrical characteristics of pathologically changed myocardium should lead to better understanding and improved clinical usefulnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 8 publications
0
24
0
1
Order By: Relevance
“…Consequently, the estimation of LV mass or LV dimensions can be imprecise. 15 The presence of LVH usually means more than an increase in LV mass and can produce, as previously stated, prolonged duration of QRS complex, left axis deviation, increased intrinsicoid deflection on left precordial leads, and intraventricular conduction defects such as left bundle-branch block (LBBB) or left anterior fascicular block.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Consequently, the estimation of LV mass or LV dimensions can be imprecise. 15 The presence of LVH usually means more than an increase in LV mass and can produce, as previously stated, prolonged duration of QRS complex, left axis deviation, increased intrinsicoid deflection on left precordial leads, and intraventricular conduction defects such as left bundle-branch block (LBBB) or left anterior fascicular block.…”
Section: Introductionmentioning
confidence: 91%
“…Because all this information can be obtained from the ECG, it appears to be inappropriate to use the ECG only for estimating LV mass. 15 As a consequence, future research should be aimed at further analyzing the relationship between these 3 components and the impact that each of them could have on prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…19 Since the hypertrophied myocardium is pathologically altered in more ways than just increase mass, it is apparent that ECG LVH has to move beyond estimation of LV mass. 20 With regards to the physiological basis for generating the ECG, it has been documented that the conduction velocity in the hypertrophied LV myocardium is slower than normal. [21][22][23] The slowing in conduction velocity is understood to be a determinant of QRS duration prolongation.…”
Section: Cmr In Understanding the Ecg In Lvhmentioning
confidence: 99%
“…The aim of this review is to provide an overview of the complex biology of left ventricular hypertrophy with an eye toward enhancing our understanding of its ECG manifestations. 3,4 Hypertrophic growth of the cardiac myocyte Whereas recent work has revealed that a small fraction of cells within the ventricle are capable of re-entering the cell cycle, 5-7 the vast majority of cardiac myocytes are postmitotic and hence do not retain the ability to divide. Rather, they respond to stress by growing, shrinking, or dying.…”
Section: Introductionmentioning
confidence: 99%